2022
DOI: 10.1038/s41401-022-01006-1
|View full text |Cite
|
Sign up to set email alerts
|

Hernandezine induces autophagic cell death in human pancreatic cancer cells via activation of the ROS/AMPK signaling pathway

Abstract: Hernandezine (Her) is a bisbenzylisoquinoline alkaloid extracted from the traditional Chinese herbal medicine Thalictrum glandulosissimum. Evidence shows that Her is a natural agonist of adenosine monophosphate (AMP)-activated protein kinase (AMPK) and induces apoptosis and autophagy in tumor cells. In this study, we investigated the role of autophagy in Her-induced cell death in human pancreatic cancer cell lines. We showed that Her dose-dependently suppressed cell proliferation, promoted autophagy and induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…4f, h ). Moreover, it is reported that intensely activated autophagy could promote cell death in PDAC 47 ; thus, we could speculate that IGF1R overexpression in nutrient deprivation could also exert a protective function in neoplastic cells, preventing an excess of autophagy. Further investigations are needed, but it is conceivable that the described mechanism could play different roles in a context-dependent manner, according to the stage of PDAC progression.…”
Section: Discussionmentioning
confidence: 95%
“…4f, h ). Moreover, it is reported that intensely activated autophagy could promote cell death in PDAC 47 ; thus, we could speculate that IGF1R overexpression in nutrient deprivation could also exert a protective function in neoplastic cells, preventing an excess of autophagy. Further investigations are needed, but it is conceivable that the described mechanism could play different roles in a context-dependent manner, according to the stage of PDAC progression.…”
Section: Discussionmentioning
confidence: 95%
“…Although there is evidence suggesting that AMPK might help cancer cells survive under certain circumstances, there is more support in the literature for the notion that AMPK acts as a tumor suppressor by leading to cell growth inhibition and cell cycle arrest [ 40 ]. Song’s study revealed that Hernandezine activates autophagy and induces autophagic cell death in PDAC cells by promoting ROS generation, activating the AMPK signaling pathway and inhibiting the mTOR/p70S6K signaling pathway [ 41 ]. Notably, activation of AMPK is dependent on the phosphorylation of AMPKα at Thr-172.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its limited selectivity, CQ targets many characteristics of lysosomes, including essential functions, at the same time, which highlights the importance of researching specific targets in the autophagylysosomal system [57]. Recently, our group showed that Hernandezine (Her) activates the ROS/AMPK signaling pathway in a concentration-dependent manner and thus induces autophagic cell death in human pancreatic cancer cells [58]. This study provided support for the application of autophagic drugs to treat pancreatic cancer, demonstrated the importance and feasibility of autophagy-related cancer therapies, and opened the door to research into therapeutic strategies by regulating key autophagy pathways.…”
Section: History Of Tfeb In the Autophagolysosomal System Lysosomal A...mentioning
confidence: 99%